Religion in Tacitus' Annals - Shannon, K (2012)
I examine how religion is presented in the Annals of Tacitus, and how it resonates with and adds complexity to the larger themes of the historian’s narrative. Memory is essential to understanding the place of religion in the narrative, for Tacitus constructs a picture of a Rome with ‘religious amnesia.’ The Annals are populated with characters, both emperors and their subjects, who fail to maintain the traditional religious practices of their forebears by neglecting prodigies and omens, committing impious murders, and even participating in the destruction of Rome’s sacred buildings. Alongside this forgetfulness of traditional religious practice runs the construction of a new memory – that of the deified Augustus – which leads to the veneration of living emperors in terms appropriate to gods. This religious narrative resonates with and illuminates Tacitean observations on the nature of power in imperial Rome. Furthermore, tracing the prominence of religious memory in the text improves our understanding of how Tacitus thinks about the past, and particularly how he thinks about the role of the historian in shaping memory for his readers. I consider various religious categories and their function in Tacitus’ writings, and how his characters interact with them: calendars (do Tacitus’ Romans preserve or change the traditional scheduling of festivals?), architecture (what determines the building of or alterations to temples and other religious monuments?), liturgy (do they worship in the same ways their ancestors did?), and images (how do they treat cult statues?). I analyze the patterns of behaviour, both in terms of ritual practice and in how Tacitus’ characters think about and interpret the supernatural, and consider how Rome’s religious past features in these patterns. The thesis is structured according to the reigns of individual emperors. Four chapters chart Tiberius’ accession, Germanicus’ death, its aftermath, and Sejanus’ rise to power; one chapter examines the religious antiquarian Claudius; and the final chapter analyzes Nero’s impieties and their consequences.